Political systems and revolution: The cases of Egypt and Tunisia / Ibrahim S.I Rabaia - Ibrahim , S.I Rabaia (2021)
Revolution in MENA is a long-term process needing a long time to correct the structural failures of the existing political systems. In other words, revolutions were created to change the status quo, pave the way to a breakthrough in the political system, and open the political sphere by introducing a more inclusive and dynamic process for entering these systems. The mismatch between inputs and outcomes in the Egyptian and Tunisian political systems produced failures in dealing with the political, economic, and social demands of the revolutionary powers in both countries. Such a failure increased the chances of success for the counter-revolutionary political structures in Egypt, who kept their positions after the revolution. The literature of the Middle East and Arab Spring studies have not yet been satisfactory in exploring the political changes and political systems of MENA, to find out why the consolidation of democracy in this context is difficult. This research aims to investigate the ability of political systems to tackle and transform sudden and unexpected shocking political events, such as revolutions. This research explores the ability of political systems to reproduce themselves based on changes in institutions and functions. Before the revolution, the political systems in Egypt and Tunisia were ambiguous in that they had limited institutions and distribution of power. Revolutions in both countries created cracks in these stable political systems and paved the way for new players who have no experience to get involved in politics. This study focuses on the relationship between the revolution and the institutions of the political system, starting from the revolutionary deadlock in the MENA. While the theoretical part of the study is based on the theory of the political system of Egyptian and Tunisian politics, the empirical part discusses the relationship between revolutions and political systems in an actor-centered approach.